Transcriptomic and Functional Studies of the RGS Protein Rax1 in Aspergillus fumigatus - Yong-Ho Choi; Min-Woo Lee; Olumuyiwa Ayokunle Igbalajobi; Jae-Hyuk Yu; Kwang-Soo Shin (Pathogens, 2019)
In the comparative transcriptomic studies of wild type (WT) and rax1 null mutant strains, we obtained an average of 22,222,727 reads of 101 bp per sample and found that 183 genes showed greater than 2.0-fold differential expression, where 92 and 91 genes were up-and down-regulated in Δrax1 compared to WT, respectively. In accordance with the significantly reduced levels of gliM and casB transcripts in the absence of rax1, the Δrax1 mutant exhibited increased sensitivity to exogenous gliotoxin (GT) without affecting levels of GT production. Moreover, Δrax1 resulted in significantly restricted colony growth and reduced viability under endoplasmic reticulum stress condition. In summary, Rax1 positively affects expression of gliM and metacaspase genes.